Development of Giziku Baik App Web-based Using Agile Method - Vilda Ana Veria Setyawati; Arif Kurniadi; Ari Yuniastuti; Oktia Woro Kasmini Handayani; Eko Farida (International Conference on Science, Education, and Technology, 2023)
In previous research, an information system based on an android application called Giziku Baik App was built. Even now, this application has entered the play store. Through e-books on stunting and adolescent nutrition. However, this application has several drawbacks, namely that cellphone owners can only use it with the Android operating system. IOS users among teenagers are increasing and dominating compared to ordinary Android phones. So the Giziku Baik App needs to be developed based on IOS or something else so anyone can use it. However, developing IOS-based applications takes a long time; sometimes, not everyone is willing and able to operate. Therefore, it is necessary to build a web-based Giziku Baik App so that it can be easily used by whoever owns the link. This study aims to develop a website-based information system for the Giziku Baik application using agile development methods. Giziku Baik App web-based used agile method to develop the information systems. Its consist of planning until demonstration. This paper show running system analysis, Giziku Baik web-based process design, database design, deployment diagram, and user interface. it can be concluded that developing a website-based Giziku Baik application using the agile developmental method can produce accurate and quality information because it uses a standardized median from the relevant ministry. In addition, users, in this case, teenagers, can use the app-based Giziku Baik to find out the results of the examination and get feedback on their nutritional status.